Traces of the sage : monument, materiality, and the first temple of Confucius - Flath, James A. (Spatial habitus (Series), 2016)
The temple of Confucius (Kong Temple) in Qufu is the definitive monument to the world's greatest sage. From its humble origins deep in China's past, the home of Confucius grew in size and stature under the auspices of almost every major dynasty until it was the largest and most richly endowed temple in the Ming and Qing empires. The decline of state-sponsored ritualism in the twentieth century triggered a profound identity crisis for the temple and its worshipers, yet the fragile relic survived decades of neglect, war, and revolution and is now recognized as a national treasure and a World Heritage Site.